Lamp: sign invented for nursing. - Porto, Fernando; Labriola, Claudia; Sousa, Sonia Regina; Silva, Gilberto Tadeu Reis da (UERJ Nursing Journal / Revista Enfermagem UERJ, 2023)
Objective: to reflect on the signs of the invented tradition of the nursing sign, known internationally as the lamp. Content: adopting the path of the theoretical essay for the sign invented for nursing, we discuss the aesthetics of the lamp, its functional morphology and lexicon (lantern, lucerne and lamp), for the purpose of its representativeness, considering the historical milestones related to it. Final considerations: understanding the implication of the sign as belonging for nursing students and professionals is to assume its direct analogy, by similarity and conventionality.